Argument is War: Relevance-Theoretic Comprehension of the Conceptual Metaphor of War in the Apocalypse - Winters, Clifford, (Linguistic Biblical Studies ;, 2020)
In Argument is War: Relevance-Theoretic Comprehension of the Conceptual Metaphor of War in the Apocalypse , Clifford T. Winters demonstrates that the apparent war in the Apocalypse is rather telling the story of the gospel : how Christ will restore Israel and, through them, the rest of the world. When Revelation is viewed through the corrective lens of cognitive linguistics, its violence becomes victory, its violent characters become Christ, and its bloody end becomes the blessed beginning of the New Jerusalem. Revelation is simply telling the story of the early church (the Gospels and Acts) to the early church, and it is using a conceptual metaphor ('ARGUMENT IS WAR') to do it.